Survival outcomes of surgical and non-surgical treatment in elderly patients with stage I pancreatic cancer: A population-based analysis - Nie, Duorui; Lan, Qingxia; Shi, Bin; Xu, Fei (Frontiers in Medicine, 2022)
Background Due to underrepresentation in randomized controlled trials among old people (≥65 years old), the effectiveness of clinical trial-based recommendations about the treatment for stage I pancreatic cancer remains controversial. In this research, we intended to investigate the different strategies of this population in surgery group and non-surgery group. Materials and methods Elderly patients aged 65 years or older with histologically diagnosed stage I pancreatic cancer from 2006 to 2017 were identified from the Surveillance, Epidemiology, and End Results (SEER) database. The included patients were divided into surgery group (receiving surgery with chemotherapy or chemoradiotherapy) and non-surgery group (receiving radiotherapy, chemotherapy, both, or neither). Overall survival (OS) and cancer-specific survival (CSS) were compared between groups by Kaplan–Meier analysis. Cox proportional hazards regression (Cox) proportional hazards regression was used to determine factors associated with survival. Results A total of 2,448 eligible patients were recruited. Among them, 18.4% were treated surgically and 81.6% were treated non-surgically. The median OS (mOS) was 26 months (95% CI: 24–30 months) in the surgery group and 7 months (95% CI: 7–8 months) in the non-surgery group. In multivariate analyses, surgery was an important factor in improving OS compared with non-surgical treatment (HR: 0.34, 95% CI: 0.29–0.39, p < 0.001). In subgroup analysis, surgery plus chemotherapy was an independent factor for OS in the surgery group, while chemoradiotherapy, chemotherapy, and radiotherapy were independent prognostic factors for patients in the non-surgery group. Conclusion Surgical resection and post-operative chemotherapy are recommended for elderly patients with stage I pancreatic cancer who can tolerate treatment, but post-operative chemoradiotherapy does not bring survival benefits compared with post-operative chemotherapy. Moreover, radiotherapy, chemotherapy, or the combination of radiotherapy and chemotherapy are significantly related to the prognosis of elderly patients with untreated pancreatic cancer, but chemoradiotherapy has the most obvious benefit.